2021
DOI: 10.1088/1361-6528/ac0b1a
|View full text |Cite
|
Sign up to set email alerts
|

A novel CaIn2S4/TiO2 NTAs heterojunction photoanode for highly efficient photocathodic protection performance of 316 SS under visible light

Abstract: Designing heterojunction photocatalysts with matched band structure and good interface contact is an effective method to improve the photoelectrochemical activity. Herein, novel CaIn2S4/TiO2 nanotube arrays (NTAs) heterojunction photoanodes were successfully prepared by electrochemical anodization and hydrothermal method. The microstructures, compositions, crystal structures, chemical valence states and light absorption performances of the composites were evaluated by field emission scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…After Lei et CIS heterojunction, the band alignments of TiO 2 and CIS lead to the establishment of a staggered type-Ⅱ heterojunction due to the relatively negative conduction band potential of CIS, which would enhance the visible-light response of TiO 2 and promote efficient charge transfer and separation, as demonstrated in previous works [22].…”
Section: Introductionmentioning
confidence: 73%
“…After Lei et CIS heterojunction, the band alignments of TiO 2 and CIS lead to the establishment of a staggered type-Ⅱ heterojunction due to the relatively negative conduction band potential of CIS, which would enhance the visible-light response of TiO 2 and promote efficient charge transfer and separation, as demonstrated in previous works [22].…”
Section: Introductionmentioning
confidence: 73%
“…Water is employed as the solvent. The morphology and size of the coatings can be controlled by adjusting the reaction temperature, reaction time, precursor solution concentration, and other experimental parameters. Wang et al prepared FeS 2 /TiO 2 heterojunction coatings through the hydrothermal method. Scanning electron microscopy (SEM) results indicated that the prepared FeS 2 adhered to TiO 2 NTs.…”
Section: Synthesis Methods Of Tio2-based Heterojunction Coatingmentioning
confidence: 99%
“…Photoelectrochemical performances of the composites were characterized by a CHI 760E electrochemical workstation (Chenhua Co., Ltd, China). The experimental setups for measuring open circuit potential (OCP), Tafel curves, electrochemical impedance spectroscopy (EIS) and photocurrent densities was the same as the devices reported previously [32]. The Mott-Schottky (M-S) plots and i-V curves were measured in 0.1 M Na 2 SO 4 solution using a conventional three-electrode system, in which Pt electrode was used as the counter electrode and a saturated calomel electrode (SCE) was used as the reference electrode, respectively.…”
Section: Photoelectrochemical Experimentsmentioning
confidence: 99%